The influencing of obesity on lung ventilation function among middle-aged and elderly people - Cui Wang; Yimin Wang; Wen Zeng; Shaomei Shang (Scientific Reports)
Abstract This study examined the effect of obesity on lung ventilation function in middle-aged and older adults using data from the China Health and Retirement Longitudinal Study. Lung function was measured using peak expiratory flow, and obesity was assessed using waist circumference and body mass index (BMI). Logistic regression and the bivariate logit model were applied to analyze the data. Among the 5631 participants, 727 were obese, 1,801 had central obesity, and 2,859 had poor pulmonary function. Individuals with obesity had a higher risk of poor pulmonary ventilation (OR = 1.869, p < 0.001) and a 12.3% decrease in the probability of good lung function (dy/dx = -0.123, p < 0.001). Moreover, individuals with a higher abdominal circumference had an increased risk of poor pulmonary ventilation (OR = 1.842, p < 0.001) and a 12.1% decrease in the probability of good lung function (dy/dx = -0.121, p < 0.001). This study indicates a negative association between obesity and lung ventilation function.